Determinants of bank efficiency: evidence from Indonesian regional development banks using data envelopment analysis - Lutfi,; Suyatno, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines the technical efficiency level of regional development banks (RDBs) in Indonesia and then analyzes the influence of bank-specific factors on this efficiency. This study uses data from all 25 conventional RDBs in Indonesia for the period 2012–2017 and a two-stage procedure to examine bank efficiency. Data Envelopment Analysis (DEA) is used to estimate bank technical efficiency and panel data techniques, both fixed effects (FE) and random effects (RE), are used to assess the determinants of bank efficiency. The results of this study indicate that most Indonesian RDBs have yet to become efficient. The most important source of their inefficiency is non-interest income. Furthermore, bank efficiency is positively influenced by capital and the loan-to-deposit ratio, while it is negatively affected by non-performing loans and the proportion of time deposits. There is also evidence that bank size has a U-shaped influence on efficiency. This study recommends that RDBs should increase the capital in improving its fee-based income through the development of innovative technology-based products and services. RDBs also need to optimize their use of depositors’ funds for lending coupled with prudential principles to avoid problem loans.